SUCCESS RATE OF ONE SESSION AND TWO SESSION TECHNIQUES FOR TREATMENT OF ASYMPTOMATIC PULPITIS OF PRIMARY TEETH WITH INDIRECT PULP CAPPING. - Rossitza Kabaktchieva; Natalia Gateva; Kremena Nikolova (Peytchinski Publishing, 2013)
Objective: Objective: To compare the success rate between the one session and two session indirect pulp capping of asymptomatic pulpitis for 1 year after the treatment was performed in children with different caries risk. Material and Methods: The children and the teeth were selected according to certain criteria for inclusion in the study. According to that, 72 children with low, moderate and high caries risk were included and 131 teeth with asymptomatic pulpitis were treated. The clinical protocols for indirect pulp capping (IPC) in one session and two sessions were defined. The review appointments were performed 6 and 12 months after the treatment using certain clinical and radiographic criteria which defined success or post-treatment complications. The results are statistically analysed using One Sided Exact Two-Proportion Test with 95% Significance level (5% risk of type I error). Results: The statistical test showed that between the compared success rates of the one session and two sessions IPC, on the 6th and 12th month, there wasn't a significant difference (p>0.05). This was valid for every one of the examined groups of patients (p>0. 05). This proves that there is no difference in the success rates of treatment of pulpitis in primary teeth using one or two sessions. Conclusions: The results about the success of treatment of asymptomatic pulpitis in primary teeth during one or two sessions have confirmed the results showed in other current studies. Our study has confirmed (clinically and radiographically) the success of both techniques and we have concluded that in children with high caries risk, more appropriate technique is the one performed in two sessions. Treatment in one session is recommended in children with low or moderate caries risk.